2014
DOI: 10.3389/fmicb.2014.00441
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between amphibians' symbiotic bacteria cause the production of emergent anti-fungal metabolites

Abstract: Amphibians possess beneficial skin bacteria that protect against the disease chytridiomycosis by producing secondary metabolites that inhibit the pathogen Batrachochytrium dendrobatidis (Bd). Metabolite production may be a mechanism of competition between bacterial species that results in host protection as a by-product. We expect that some co-cultures of bacterial species or strains will result in greater Bd inhibition than mono-cultures. To test this, we cultured four bacterial isolates (Bacillus sp., Janthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 32 publications
0
101
0
2
Order By: Relevance
“…In addition, the relative abundance of these OTUs may have increased because Bd was able to negatively affect the abundance of other OTUs [57]. Facilitation of Bd growth and colonization could occur either when symbiotic bacteria shift their metabolite profiles in a way that favours Bd [35] or by reducing the capability of other microbes to inhibit Bd. In a recent study, bacteria isolated from cyclamen and tomato plants, including a Novosphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relative abundance of these OTUs may have increased because Bd was able to negatively affect the abundance of other OTUs [57]. Facilitation of Bd growth and colonization could occur either when symbiotic bacteria shift their metabolite profiles in a way that favours Bd [35] or by reducing the capability of other microbes to inhibit Bd. In a recent study, bacteria isolated from cyclamen and tomato plants, including a Novosphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites produced by amphibian cutaneous bacteria can inhibit Bd in vitro [13,34,35] and in vivo [11] . Therefore, we excised and extracted the skin of each frog to obtain cutaneous metabolites following procedures described by Brucker et al [13]; briefly, excised skins were extracted three times by shaking in HPLC-grade methanol (5 ml each extraction).…”
Section: (E) Extraction Of Cutaneous Metabolites and Lcmsmentioning
confidence: 99%
“…Studies have repeatedly illustrated the importance in a complex microbiome for resilience of the community in response to a pathogenic infection (33)(34)(35). A bacterial consortium approach that treats microbiomes as a suite of functional traits rather than a substrate for the insertion of candidate bacteria is likely to offer a more comprehensive protection of hosts from B. dendrobatidis and other threatening amphibian pathogens (12,28,36). How the different members of such consortia will be determined is currently unknown, but our results highlight the limitations of a taxonomic approach for understanding what bacterial communities may afford resistance to B. dendrobatidis: both species and genus showed a limited potential to identify potentially inhibitory bacteria in our study.…”
Section: Figmentioning
confidence: 99%
“…Multistrain mixtures have also been considered, since a wider variety of antipathogen secretions are expected. In addition, different strains in competition can produce antipathogenic secretions, which are not produced through growth alone . A study in mice found that a mixture of six bacteria cured C .…”
Section: Next Steps In Probiotics Research and Application For Wildlimentioning
confidence: 99%